The Importance of Analyzing Child Development and Understanding of Milk-Based Fortified Foods for Primary Health Care Issue - Noor Diah Erlinawati; Sumarsih Sumarsih; Hilda Taurina (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
Indonesia is already facing a high nutritional problem. Early detection of child wasting is the key to successful prevention and treatment. Increasing animal protein intake for children is one of the government's steps to address child malnutrition. Consumption of fortified milk as one of the animal proteins may support the growth and development of children. The general purpose of this community service is to increase the knowledge and the implementation of dairy products to improve child immunity and growth. This community service activity was carried out at the Sidodadi village hall, Central Bengkulu in 2021. Participants in the community service activity were maternal and child village health workers, plus representatives from the Puskesmas and village officials with a total of 32 participants. The methods used are socializing information, questions and answers with participants based on experience and field findings, providing materials related to sources of milk food ingredients and their fortification, carrying out copyright quizzes on milk-based healthy food recipes, and monitoring with evaluation. Evaluation sheets are used to assess participant satisfaction and record things that are still needed by cadres for further socialization activities. The performance test was carried out with a quiz on preparing healthy milk-based food recipes for children. Activity results are described with a satisfaction survey. Increasing education through health counseling greatly influences the knowledge of village health worker to be wise in providing education on fortified milk-based foods and providing examples of useful recipes for malnourished children.